Debiasing competitive irrationality: How managers can be prevented from trading off absolute for relative profit - Graf-Vlachy, Lorenz; König, Andreas; Enders, Albrecht (European Management Journal, 2012)
Managers sometimes sacrifice profits only to improve their relative competitive standing, a behaviour that is known as "competitive irrationality." Previous research has generated a wealth of insight into the general foundations of this often dysfunctional type of managerial decision-making. However, almost no attention has been devoted to the question of how managers can reduce competitive irrationality. We address this issue by adopting the logic of debiasing research to hypothesize about five potential countermeasures: creating accountability, "considering the opposite," making the bias of competitive irrationality salient to the decision maker, reducing time pressure and relying on external advice. We test our hypotheses on a sample of 934 managers using web-based experiments. Our empirical evidence supports our call for reducing time pressure in managerial decision-making and for providing managers with training in biases to attenuate competitive irrationality. However, our data also indicate that efforts to make managers feel accountable for their actions can have a detrimental effect on decision quality, which is contrary to our theorizing. © 2011 Elsevier Ltd.
WiSo-Import:2015-03-26:3221
Keywords: Profit; Irrationality; Competitive